Computational Investigation of Intense Short-Wavelength Laser Interaction with Rare Gas Clusters - Bigaouette, Nicolas (Université d'Ottawa / University of Ottawa, 2014)
Clusters of atoms have remarkable optical properties that were exploited since the antiquity. It was only during the late 20th century though that their production was better controlled and opened the door to a better understanding of matter. Lasers are the tool of choice to study these nanoscopic objects so scientists have been blowing clusters with high intensities and short duration laser pulses to gain insights on the dynamics at the nanoscale. Clusters of atoms are an excellent first step in the study of bio-molecules imaging. New advancements in laser technology in the shape of Free Electron Lasers (FEL) made shorter and shorter wavelengths accessible from the infrared (IR) to the vacuum and extreme ultra-violet (VUV and XUV) to even X-rays. Experiments in these short wavelengths regimes revealed surprisingly high energy absorption that are yet to be fully explained. This thesis tries to increase the global knowledge of clusters of rare-gas atoms interacting with short duration and high intensity lasers in the VUV and XUV regime. Theoretical and numerical tools were developed and a novel model of energy transfer based on excited states will be presented. The first part describes the current knowledge of laser-cluster interaction in the short wavelength regime followed by the description of the new model. In the second part of the thesis the different tools and implementations used throughout this work are presented. Third, a series of journal articles (of which four are published and one to be submitted) are included where our models and tools were successfully used to explain experimental results.
Keywords: rare gas clusters; computational; laser; short wavelength